Inflammation in the pathogenesis of microvascular complications in diabetes - Nguyen, Dung V.; Shaw, Lynn; Grant, Maria (Frontiers in Endocrinology, 2012)
Diabetes and hyperglycemia create a proinflammatory microenvironment that progresses to microvascular complications such as nephropathy, retinopathy, and neuropathy. Diet-induced insulin resistance is a potential initiator of this change in Type 2 diabetes (T2D) which can increase adipokines and generate a chronic low-grade inflammatory state. The advanced glycation end-products (AGEs) AGE receptor (RAGE) axis, reactive oxygen species, and hypoxia can also interact to worsen complications. Numerous efforts have gained way to understanding the mechanisms of these modulators and attenuation of the inflammatory response, however effective treatments have still not emerged. The complexity of inflammatory signaling may suggest a need for multi-targeted therapy. This review presents recent findings aimed at new treatment strategies.